The Impact of Renewable Energy Consumption and Public Capital Expenditure on Poverty Reduction in Nigeria - Balogun, Afolabi; Oloja-Ojabo, Ene Debra (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
Poverty has been an important issue of discussion in underdeveloped countries and has been of crucial concern to many stakeholders across the globe. This article examines the extent to which renewable energy consumption and public capital expenditure impact the poverty rate in Nigeria over the period 2003 - 2019. We employed cointegration and Autoregressive Distributed Lag (ARDL) bounds model for our analysis. Our results revealed that renewable energy consumption significantly escalates poverty in the short run. Public capital expenditure, economic growth, and governance quality substantially reduce Nigeria's poverty. The long-run analysis reveals that renewable energy consumption significantly elevates Nigeria's poverty rate in the long run. Moreso, economic growth and quality of governance reduce the poverty rate substantially, whereas public capital expenditure does not significantly reduce the poverty rate in Nigeria in the long run. The Nigerian government was recommended to adopt modern renewable sources through a public-private partnership and promote good governance, especially in the efficient and appropriate implementation of public capital expenditures.